(untitled) (Cambridge, 2003)
This is a collection of original essays by some of the leading moral and political thinkers of our time on the ethical and legal implications of humanitarian military intervention. It presents a variety of normative perspectives on topics such as the just-war theory and its limits, secession and international law, and new approaches toward the moral adequacy of intervention. They form a challenging and timely volume that will interest political philosophers, political theorists, readers in law and international relations, and anyone interested in the moral dimensions of international affairs.
Keywords: Intervention (International law),Can thiệp (pháp luật quốc tế); Moral and ethical aspects,Khía cạnh đạo đức